ADOPSI E-COMMERCE DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) BAGI UMKM AGRIBISNIS DI KABUPATEN BANTUL - Pusfitaningrum, Mayfilda; Agustono, Agustono; Khomah, Isti (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2021)
This research aims to analyze the factors that are influential in the adoption of e-commerce by agribusiness MSMEs in Bantul Regency which is carried out by adopting the Technology Acceptance Model (TAM). The selection of locations was carried out purposely on the consideration of Bantul Regency has the highest number of MSMEs in Yogyakarta Province and has been implemented digital MSME program. Sampling was conducted by purposive sampling which amounted to 135 respondents with the criteria of agribusiness MSMEs domiciled in Bantul Regency who already use e-commerce in their business activities. The data analysis used is SEM-PLS which is operated using SmartPLS 3.0 software. The results showed that computer self-efficacy has a positive influence on perceived ease of use and perceived usefulness. Perceived ease of use has a positive influence on perceived usefulness and attitude towards using. Perceived usefulness has a positive influence on attitude towards using and intention to use. Attitude towards using has a positive influence on intention to use. Intention to use has a positive influence on actual use in the adoption of e-commerce in Agribusiness MSMEs in Bantul Regency.